PELATIHAN PROMOSI PRODUK, PELAYANAN DAN KEPUASAN PELANGGAN UMKM GOFOOD - Dani, Suci Rahma; Hertati, Lesi; Terrtiavini, Terrtiavini; Heryati, Agustina; Cahyani, Nani; Puspitawati, Lilis (Transpublika Publisher, 2024)
The purpose of this research is to evaluate the impact of product promotion, service, and customer satisfaction training on the competitiveness of SMEs on the Go-Food platform. Additionally, this research aims to identify strategies that can enhance visibility, sales, and customer loyalty. The research methods used include analyzing product quality, service quality, promotion, and customer satisfaction. This approach includes the use of social media, SEO, paid advertising, and loyalty programs. Data was collected through surveys and customer feedback. The research findings indicate that effective training in product promotion and service can improve customer satisfaction and the competitiveness of SMEs. The implementation of strategies such as the use of social media and loyalty programs has proven to increase visibility and sales. Quick and professional responses to customers, as well as maintaining cleanliness standards and product quality, also contribute positively. Therefore, it can be concluded that training on product promotion, service, and customer satisfaction is crucial for enhancing the competitiveness and success of SMEs on the Go-Food platform. With the right strategies, SMEs can achieve long-term growth and improve customer loyalty.